NEO-RENAISSANCE AND REVITALIZATION OF VOTIC – WHO CARES? - Heinike Heinsoo; Margit Kuusk (2011)
The paper deals with the reason for the decline of the Votic language and neo-renaissance and revitalization of the Votic.The reason for the decline of the Votic language are the small number of people, traditionally sparse population and the assimilation – the speakers of Votic have always lived in the sphere of influence of the Russian language and culture. The reasons for neo-renaissance are the collapse of the Soviet Union, a general trend to look for one’s roots, enthusiastic votophiles and the local activities. In the earlier times Votic national movement originated from local people, but recently there has been interest in the Votic affairs on the state level.The plans for the near future are under common title the Votic project.